RENEWED ISLAMIC MOVEMENT IN THE PRESS: Case Study of “Ruangan Agama” Rubric in Indonesia Raya Newspaper (1949-1955) (JOURNAL OF INDONESIAN ISLAM, 2024)
The era of Liberal Democracy (1950-1959) was a period of political dynamics in which Islamic political parties had a significant role at the time, such as the Masjumi Party and the Nahdlatul Ulama Party. However, in addition to political parties, newspaper is another medium used to promote Islam as a way of life. This article analyzes the column “Ruangan Agama” in the Indonesia Raya newspaper published between 1949 to 1959 in promoting Islam to the public. It is a non-partisan newspaper and not the official media of any party as well. The method used is qualitative and historical approach to get a comprehensive and complete picture of Islamic thought at that time. The findings illustrate that the rubric of the "Ruangan Agama" in Indonesia Raya has engaged a discussion of contextual religion by raising real issues that were relevant at that time through the engaged reflection of Muslim intellectuals. The issues raised by the “Ruangan Agama” rubric are corruption, poverty, abuse of power, and others. In short, the "Ruangan Agama" Indonesia Raya’s column is part of a renewed Islamic movement that reflects critically on the fate of Muslims within the nation-state.